Kajian Implementasi Kesehatan dan Keselamatan Kerja Dengan Pendekatan Behavior Based Safety - Fitri Agustina; Nachnul Ansori; Trisita Novianti; Miftakhul Farikha (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
This study discusses about how to evaluate the implementation of occupational health and safety (OHS) on batik small and medium sized enterprises in Madura. Successful implementation of OHS is influenced by worker behavior and then is measured by a score of worker safety through the intervention program. Intervention program is designed by using behavior-based safety approach that is based on the identification of hazards and risks at workplace. Intervention program is conducted by the provision of personal protective equipment, work standard setting, supervision and understanding improvement of the OHS. The results show that interventions can improve worker safety score from 34% to 56%.